High-damping base material as well as preparation method and application thereof

By reasonably proportioning a variety of materials, a high-dampening bottom material was developed, which solved the problem of insufficient brake noise reduction in the prior art, achieved high strength, high damping and low noise effects, and ensured the stability and comfort of braking.

CN119899435AActive Publication Date: 2025-04-29HUNAN JINLI HIGH TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510390788.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The prior art has shortcomings in reducing vehicle braking noise, and the added damping noise-reducing materials can easily lead to thermal decline, increase wear or reduce braking comfort.

Method used

Develop a high-damping base material to form a friction material with high strength, high damping and low noise characteristics by reasonably proportioning nitrile rubber, phenolic resin powder, composite reinforcement fibers, fillers, compatibilizers and curing accelerators.

Benefits of technology

It realizes that without losing the friction and wear performance of the friction plate, it significantly reduces braking noise, improves the stability and wear resistance of the friction plate, and ensures braking comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899435A_ABST
    Figure CN119899435A_ABST
Patent Text Reader

Abstract

The invention discloses a high-damping backing material and a preparation method and application thereof, and relates to the technical field of brake materials, the high-damping backing material comprises the following preparation raw materials by mass: 10-40 parts of nitrile rubber, 4-10 parts of phenolic resin powder, 30-50 parts of composite reinforced fibers, 0.5-5 parts of zinc powder, 10-40 parts of a filler, 0.6-2.3 parts of a compatilizer, and 0.2-4 parts of a curing accelerator; the composite reinforced fibers comprise para-aramid pulp, porous hydrated calcium silicate and metal fibers; wherein the mass ratio of the para-aramid pulp to the porous hydrated calcium silicate to the metal fibers is 1: (2-7): (3-10); the metal fibers comprise, by mass, 5-30% of brass fibers, 3-20% of aluminum fibers and the balance steel wool. The prepared high-damping backing material has the characteristics of high strength, high damping and low noise.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brake materials, and in particular relates to a high-damping base material and a preparation method and application thereof. Background Art

[0002] Automobile friction pads are the core components of the braking system. When braking, the pedal force is amplified through the brake pipe to form hydraulic pressure, which pushes the friction pad to contact the brake disc and generate friction, thereby achieving vehicle deceleration or stopping. This process belongs to dry friction, but due to the difference in material between the friction pad and the brake disc, the change in pedal force, the difference in temperature and the difference in braking speed, brake tremor often occurs, which in turn causes noise and abnormal sound.

[0003] In order to solve the problem of brake noise, the industry has taken a variety of measures: first, developing friction plates with different material formulas, such as semi-metallic, low-metallic and metal-free friction plates, to reduce the noise between the cast iron brake disc and the metal iron content; second, adding damping noise reduction materials such as nitrile rubber powder, vermiculite powder and hollow glass beads to the friction plate; third, sticking damping rubber sheets on the steel back of the friction plate. Although these methods can reduce noise to a certain extent, they cannot completely eliminate it and there are some risks. For example, adding too much nitrile rubber powder will cause thermal decay, too much vermiculite will increase wear, and a high proportion of hollow glass beads will make the friction coefficient too high, thereby reducing the comfort of braking. Summary of the invention

[0004] In order to overcome the technical problems of brake noise and abnormal sound, the present invention provides a high damping base material and a preparation method and application thereof. The high damping base material prepared by the present invention has the characteristics of high strength, high damping and low noise without losing the friction and wear performance of the friction plate.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] The invention provides a high damping base material, comprising the following raw materials in parts by weight: 10 to 40 parts of nitrile rubber, 4 to 10 parts of phenolic resin powder, 30 to 50 parts of composite reinforcing fiber, 0.5 to 5 parts of zinc powder, 10 to 40 parts of filler, 0.6 to 2.3 parts of compatibilizer, and 0.2 to 4 parts of curing accelerator; Preferably, the high damping base material comprises the following raw materials in parts by mass: 20-30 parts of nitrile rubber, 5-9 parts of phenolic resin powder, 35-46 parts of composite reinforcing fiber, 1-4 parts of zinc powder, 15-32 parts of filler, 0.6-1.8 parts of compatibilizer and 0.2-3 parts of curing accelerator; The brass fiber and steel wool are soaked in a silane coupling agent and then dried, and then aluminum fiber is added and mixed to obtain metal fiber; The fiber length of the para-aramid pulp is 0.5-1.5 mm, preferably 0.7-1.4 mm; The fiber specific area of ​​the para-aramid pulp is 5 to 13 m 2 / g; The density of the para-aramid pulp is 1.42-1.46 g / cm 3 ; The chemical composition of the steel wool includes, by mass, C: 0.07-0.12%, Si≤0.07%, Mn: 0.8-1.25%, S≤0.03%, P≤0.03%; The brass fiber has a tapped volume of 0.5-0.8 mL / g; The outer diameter of the aluminum fiber is 8-30 μm, preferably 20-30 μm; The elongation of the aluminum fiber is ≥2%.

[0007] The composite reinforcing fiber comprises para-aramid pulp, porous hydrated calcium silicate and metal fiber; wherein the mass ratio of the para-aramid pulp: the porous hydrated calcium silicate: the metal fiber is 1:2-7:3-10, preferably 1:2-5:4-7; In terms of mass fraction, the metal fiber consists of 5-30% brass fiber, 3-20% aluminum fiber and the balance steel wool; preferably, the metal fiber consists of 12-26% brass fiber, 7-16% aluminum fiber and the balance steel wool.

[0008] In the present invention, the phenolic resin powder is a thermosetting phenolic resin or a modified phenolic resin powder; Wherein, the modified phenolic resin powder is rubber modified phenolic resin powder, silicon modified phenolic resin powder, cashew nut shell oil modified phenolic resin powder; preferably cashew nut shell oil modified phenolic resin powder; Cashew nut shell oil modified phenolic resin powder can effectively absorb vibration friction energy and reduce the occurrence of noise by adjusting the porosity and thermal expansion coefficient of the friction material.

[0009] In the present invention, the particle size of the phenolic resin powder is ≤75 μm.

[0010] In the present invention, the filler is at least one of barium sulfate, calcium carbonate, mica powder and zinc oxide.

[0011] In the present invention, the particle size of the filler is ≤45 μm.

[0012] The composite reinforcing fibers form a rigid fiber network with an aspect ratio in the rubber matrix, which can improve the rubber matrix's dissipation of external friction vibration energy, reduce vibration amplitude, and thus reduce braking noise.

[0013] In the present invention, the compatibilizer is a maleic anhydride grafted compatibilizer or a silane coupling agent; preferably, it is a maleic anhydride grafted compatibilizer; preferably, the maleic anhydride grafted compatibilizer is a maleic anhydride grafted ABS blend.

[0014] The maleic anhydride grafted compatibilizer can enhance the bonding force between nitrile rubber and inorganic fillers or fibers; at the same time, it can also react with phenolic resin powder to improve the interfacial adhesion between phenolic resin powder and composite reinforcing fibers; and improve the interfacial tension between composite reinforcing fibers and the matrix, making the composite reinforcing fibers more evenly distributed in the matrix.

[0015] In the present invention, the curing accelerator is a hexamethylenetetramine curing accelerator.

[0016] In the present invention, the raw materials for preparing the high damping base material further include an auxiliary agent, and the auxiliary agent is at least one of a colorant, a flame retardant and an antioxidant.

[0017] Furthermore, the auxiliary agent includes 0-7 parts of a colorant, 0-2 parts of a flame retardant and 0-3 parts of an antioxidant, calculated by weight.

[0018] In the present invention, the dye is carbon black, iron black, iron red or chrome green.

[0019] In the present invention, the flame retardant is at least one of antimony trioxide, decabromodiphenylethane, aluminum dihydrogen tripolyphosphate, and zinc borate.

[0020] In the present invention, the antioxidant is an arylamine antioxidant; preferably, the antioxidant is a diarylamine antioxidant, a p-phenylenediamine antioxidant or a p-phenylenediamine antioxidant.

[0021] The present invention provides a method for preparing the high damping base material as described above, comprising the following steps: S1. Pre-treating brass fiber and steel wool, and then adding aluminum fiber to the mixture to obtain metal fiber: the pre-treatment is to soak the brass fiber and steel wool in a silane coupling agent with a mass fraction of 5-10% for 5-10 minutes and then dry the pre-treatment; S2. The nitrile rubber is plasticized, and then the other raw materials for preparing the high damping base material are subjected to low-temperature mixing, calendering and cooling to obtain a rubber block; S3. The rubber blocks are crushed and sieved to obtain high damping base material.

[0022] The silane coupling agent is KH550, KH560 or KH570.

[0023] Silane coupling agent can improve the corrosion resistance of metal fiber and also improve the bonding force between metal fiber and other components.

[0024] In the present invention, the low-temperature banburying and the plasticizing are both carried out in an internal mixer, and the temperature in the internal mixer chamber during the low-temperature banburying and plasticizing is ≤120°C; The rotating speed of the internal mixer is 10-80 rpm, preferably 20-50 rpm; The filling factor of the internal mixer is 0.8 to 2.5 times, preferably 1.0 to 1.5 times; The compacting pressure of the internal mixer is 0.5-1.5 MPa, preferably 0.6-0.8 MPa.

[0025] In the present invention, the time of plasticating is 5 to 20 minutes, preferably 5 to 10 minutes.

[0026] In the present invention, the low-temperature banburying time is 5 to 30 minutes, preferably 10 to 20 minutes.

[0027] In the present invention, the roller speed of the calendering molding is 25-60 rpm.

[0028] In the present invention, the roller temperature of the calendering molding is 50-90°C.

[0029] In the present invention, the roller distance of the calendering molding is 0.5-2 mm.

[0030] In the present invention, the cooling water temperature used for cooling is 20-30°C.

[0031] In the present invention, the particle size of the sieve is ≤3 mm.

[0032] The present invention also provides the use of the high damping base material or the high damping base material obtained by the preparation method in a friction plate, wherein the friction plate comprises a steel back, the high damping base material and a friction material fabric from bottom to top.

[0033] In the present invention, the thickness of the steel back is 4-6 mm; the thickness of the high damping base material is 2-2.5 mm; and the thickness of the friction material surface is 8-15 mm.

[0034] In the present invention, the preparation of the friction plate comprises the following steps: spreading the high damping base material and the friction material surface material flat and covering them on the surface of the glue-coated steel back, and then performing hot pressing and curing to obtain the friction plate.

[0035] Furthermore, the hot pressing temperature is 130-160°C, the pressure is 30-50 MPa°C, and the time is 3-8 min.

[0036] Furthermore, the curing temperature is 200-230° C., and the curing time is 8-12 hours.

[0037] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0038] Compared with the prior art, the present invention has the following beneficial effects: 1. The aramid pulp in the composite reinforcing fiber in the high damping base material of the present invention affects the friction coefficient and the wear rate. Adding too much will cause the friction coefficient to no longer change significantly, and may even reduce the surface adsorption area, increase wear, and reduce interface adhesion due to particle aggregation. Polyhydrated calcium silicate has a large specific surface area and a porous structure, which can adsorb and disperse other fillers, improve the uniformity and stability of the friction material, and enhance thermal stability. Metal fiber reinforces the hardness and toughness of the material, and improves wear resistance and thermal conductivity. It can form a non-continuous fiber network when dispersed in the rubber matrix, enhance the strength and stiffness of the matrix, absorb and dissipate vibration energy, thereby improving damping and reducing noise. By rationally matching aramid pulp, polyhydrated calcium silicate and metal fiber, the performance of the friction material can be optimized, and a balance between low noise, high stability and good wear resistance can be achieved.

[0039] 2. The steel fiber in the metal fiber provides high strength and wear resistance, the brass fiber provides corrosion resistance and thermal stability, and the aluminum fiber balances the friction coefficient and adaptability. The combination of the three makes the friction material more stable when subjected to impact, shear and centrifugal forces.

[0040] 3. The friction plate prepared by the high damping base material of the present invention has high shear strength and high damping characteristics. The shear strength at room temperature (23±5°C) is ≥6.4MPa, and in some preferred embodiments, it is 6.4~7.0MPa; the shear strength at high temperature (300±5°C) is ≥3.64MPa, and in some preferred embodiments, it is 6.4~4.0MPa. The probability of the friction pair assembled by the friction plate emitting a noise of >70Db is ≤2.3%, and in some preferred embodiments, it is 1.1~2.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a microscopic image of the high damping base material prepared in Example 1.

[0042] Figure 2 It is a structural schematic diagram of high damping base material.

[0043] Figure 3 Schematic diagram of the structure of the friction plate prepared with high damping base material. DETAILED DESCRIPTION

[0044] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0045] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0046] The nitrile rubber used in the following examples is LG (Korea) Chem NBR 6250, and the nitrile rubber is a high acrylonitrile type nitrile rubber; The cashew nut shell oil modified phenolic resin powder was purchased from Shandong Yonghui New Materials Co., Ltd., and the model number was PF-221 or PF-222; the urotropine content of the cashew nut shell oil modified phenolic resin powder was 8-9%, and the D95 was 250 mesh; Anti-aging agent: the model is antioxidant DNP (diarylamine antioxidant), antioxidant IPPD (paraphenylenediamine antioxidant) or antioxidant 6PPD (paraphenylenediamine antioxidant); Para-aramid pulp was purchased from DuPont Kevlar 1F538 in the United States. The specific gravity of the para-aramid pulp is 1.45 g / cm 3 , fiber length is 1.00~1.34mm, fiber specific surface area is 5~11m 2 / g; Porous hydrated calcium silicate was purchased from Jiangxi Dishi Mineral Fiber Technology Co., Ltd.; Steel wool was purchased from Dezhou Fangyuan Steel Wool Fiber Co., Ltd. D0-160. The chemical composition of steel wool is C: 0.07~0.12%, Si≤0.07%, Mn: 0.8~1.25%, S<0.03%, P<0.3%; Brass fiber was purchased from Zhangjiagang Xinli Metal Co., Ltd. SB-1060. Brass fiber was crushed brass fiber with a compaction volume of 0.5~0.8mL / g; Aluminum fiber was purchased from Jiangsu Worldshine Mould Technology Co., Ltd. The aluminum fiber is a continuous micron-grade metal aluminum fiber with a grade of 1060. The outer diameter of the aluminum fiber is 20-30 μm and the elongation of the aluminum fiber is ≥2%. Compatibilizer: Maleic anhydride grafted compatibilizer was purchased from Ketong Plastic KT-3, which is a blend of maleic anhydride grafted ABS; Curing accelerator: hexamethylenetetramine curing agent.

[0047] The microscopic image was measured using the KEYENCE 3D ultra-depth digital microscope VHX-X1.

[0048] [High damping friction base material and preparation method thereof]

[0049] Example 1 The high damping base material formula of the high damping of the present embodiment is as follows: The high damping base material is composed of the following raw materials in parts by mass: 22 parts of nitrile rubber, 5 parts of phenolic resin powder, 46 parts of composite reinforcing fiber, 1 part of zinc powder, 23 parts of filler, 3 parts of colorant (carbon black), 1.8 parts of compatibilizer and 0.7 parts of curing accelerator; In this embodiment, the phenolic resin powder is cashew nut shell oil modified phenolic resin powder; In this embodiment, the mass ratio of para-aramid pulp: porous hydrated calcium silicate: metal fiber in the composite reinforcing fiber is 1:2.5:4.2; In this embodiment, the metal fiber is composed of 23% brass fiber, 15% aluminum fiber and the balance steel wool by mass fraction; In this embodiment, the filler is 20 parts of barium sulfate and 3 parts of zinc chloride.

[0050] The preparation method of the high damping friction base material of this embodiment is as follows: S1. Soak brass fiber and steel wool in 8% by mass silane coupling agent (KH560) for 6 minutes and then dry; after drying, add aluminum fiber and mix to obtain metal fiber; S2. The speed of the internal mixer is 30rpm, the filling factor is 1.2 times, the compacting pressure is 0.6MPa, and the temperature in the internal mixer is controlled at 110℃. If the temperature is too high, water can be added to adjust the temperature. The addition of water can form pores in the rubber compound and promote the mutual penetration and bonding of rubber, fillers and other raw materials. Add nitrile rubber to the internal mixer and plasticize for 10 minutes, then add other raw materials in the high damping base material and perform low temperature internal mixing for 15 minutes; The mixture was then calendered on an open mill with a roller temperature of 60°C, a roller speed of 35 rpm, and a roller distance of 1.2 mm. The mixture was then cooled with a cooling temperature of 25°C and a cooling speed ratio of 1:1.17. A rubber block was obtained after cooling. The rubber block is crushed and screened to obtain high damping base material, and the screening particle size is ≤3mm.

[0051] The microscopic photo of the high damping friction base material prepared in this embodiment is shown in Figure 1 (The scale bar in the figure is 500μm). See the structural diagram Figure 2 , nitrile rubber acts as a matrix to provide flexibility and elasticity; para-aramid pulp is dispersed in the nitrile rubber matrix to form a network support structure; metal fibers and organic fibers are interwoven to form a "rigid and flexible" composite reinforcement system; porous hydrated silicate is combined with other components due to its porous and high specific surface structure to form a heat-resistant barrier to inhibit thermal decay; other powder materials such as phenolic resin powder, filler, zinc powder, etc. are evenly dispersed in the matrix, and the surface properties of the material are optimized by micro-filling, which can balance the friction coefficient and improve the strength and damping performance.

[0052] Example 2 The difference between this embodiment and embodiment 1 is that: The high damping base material formula of this embodiment is as follows: 27 parts of nitrile rubber, 8 parts of phenolic resin powder, 38 parts of composite reinforcing fiber, 1.5 parts of zinc powder, 17 parts of filler, 1.5 parts of compatibilizer, and 2.8 parts of curing accelerator. The phenolic resin powder used in this embodiment is thermosetting phenolic resin powder purchased from Hangmo New Materials Co., Ltd. F2123-3.

[0053] Other steps and parameters are the same as in Example 1.

[0054] Example 3 The difference between this embodiment and embodiment 1 is that: The high damping base material formula of this embodiment is: 30 parts of nitrile rubber, 7 parts of phenolic resin powder, 35 parts of composite reinforcing fiber, 2.8 parts of zinc powder, 24 parts of filler, 1.8 parts of compatibilizer and 2.2 parts of curing accelerator. In this embodiment, the mass ratio of para-aramid pulp: porous hydrated calcium silicate: metal fiber in the composite reinforcing fiber is 1:3.5:5.4.

[0055] Other steps and parameters are the same as in Example 1.

[0056] Example 4 The difference between this embodiment and embodiment 1 is that: The high damping base material formula of this embodiment is: 25 parts of nitrile rubber, 8 parts of phenolic resin powder, 42 parts of composite reinforcing fiber, 2.2 parts of zinc powder, 28 parts of filler, 3.7 parts of colorant (carbon black), 1.1 parts of compatibilizer and 2.3 parts of curing accelerator. Calculated by mass fraction, the metal fiber of this embodiment is composed of 12% brass fiber, 16% aluminum fiber and the remainder steel wool.

[0057] Other steps and parameters are the same as in Example 1.

[0058] Example 5 The high damping base material formula of the high damping of the present embodiment is as follows: The high damping base material is composed of the following raw materials in parts by mass: 22 parts of nitrile rubber, 5 parts of phenolic resin powder, 46 parts of composite reinforcing fiber, 1 part of zinc powder, 23 parts of filler, 3 parts of colorant (carbon black), 1.8 parts of compatibilizer, 2.7 parts of antioxidant (antioxidant DNP), 1.5 parts of flame retardant (decabromodiphenyl ethane) and 0.8 parts of curing accelerator; In this embodiment, the filler is 20 parts of barium sulfate and 8 parts of calcium carbonate.

[0059] Other steps and parameters are the same as in Example 1.

[0060] Example 6 The difference between this embodiment and embodiment 1 is that: The metal fiber of this embodiment is not pretreated. S1: brass fiber, aluminum fiber and steel wool are directly mixed to obtain metal fiber.

[0061] Other steps and parameters are the same as in Example 1.

[0062] Comparative Example 1 The difference between this comparative example and Example 1 is: The composite reinforcing fiber of this comparative example does not contain porous hydrated calcium silicate, and the mass ratio of aramid pulp to metal fiber in the composite reinforcing fiber is 1:4.2.

[0063] Other steps and parameters are the same as in Example 1.

[0064] Comparative Example 2 The difference between this comparative example and Example 1 is: The composite reinforcing fiber of this comparative example does not contain metal fiber, and the mass ratio of aramid pulp to porous hydrated calcium silicate in the composite reinforcing fiber is 1:2.5.

[0065] Other steps and parameters are the same as in Example 1.

[0066] Comparative Example 3 The difference between this comparative example and Example 1 is: In the composite reinforced fiber aramid pulp of this comparative example, the mass ratio of porous hydrated calcium silicate to metal fiber in the composite reinforced fiber is 2.5:4.2.

[0067] Other steps and parameters are the same as in Example 1.

[0068] Comparative Example 4 The difference between this comparative example and Example 1 is: The mass ratio of aramid pulp: porous hydrated calcium silicate: metal fiber in the composite reinforced fiber of this comparative example is 5:2.5:4.2.

[0069] Other steps and parameters are the same as in Example 1.

[0070] Comparative Example 5 The difference between this comparative example and Example 1 is: Calculated by mass fraction, the metal fiber of this comparative example consists of 33% brass fiber and the remainder steel wool.

[0071] Other steps and parameters are the same as in Example 1.

[0072] Comparative Example 6 The difference between this comparative example and Example 1 is: Calculated by mass fraction, the metal fiber of this comparative example consists of 3% brass fiber, 25% aluminum fiber and the balance steel wool.

[0073] Other steps and parameters are the same as in Example 1.

[0074]

Friction plate

[0075] The high damping base materials prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were processed into friction plates 1 to 6 and comparative friction plates 1 to 6 respectively; the preparation process of the high damping base materials into friction plates is as follows: The friction material fabric is prepared by weight ratio: 7 parts of solvent-free cashew resin (Calider NX-4778), 3 parts of cashew nut shell oil friction powder (Calider NX-2020-30), 2 parts of para-aramid pulp, 30 parts of potassium titanate fiber (KS-WTS-1 of Bengbu Guoti Nanomaterial Co., Ltd.), 13 parts of barium sulfate, 20 parts of zirconium oxide and 15 parts of artificial graphite; Pour the friction material surface and high damping base material into the steel membrane cavity in turn, then place the glue-coated steel back on the surface of the high damping base material layer, start the hot press, the hot pressing temperature is 150℃, the pressure is 40MPa, and the hot pressing time is 4min; Then cure in an oven for 9 hours at a curing temperature of 230°C; The steel backing thickness of the friction plate and the comparison friction plate is 6 mm, the thickness of the high damping base material is 2 mm, and the thickness of the friction material surface is 10 mm.

[0076] Comparison friction plate 7 The difference between this comparative friction plate and friction plate 1 is: The friction plate of this comparative example is composed of a steel back and a friction material fabric; The comparative friction plate 8 obtained by processing does not use high damping base material in the preparation process, and is composed of a 6 mm steel back and a 12 mm friction material surface.

[0077]

Friction plate performance test

[0078]

[0079] The frequency-damping characteristics are tested according to the SAE J2598-2020 standard. The testing equipment is: Jurid-01 natural frequency-damping characteristics tester. The DPR value (Damping rate) indicates the energy dissipation capacity of the material under dynamic load. The higher the DPR value, the more energy the material dissipates during deformation and the better the damping performance. Materials with high DPR values ​​can absorb vibration and impact more effectively and can also effectively reduce noise in automobile friction braking.

[0080] Test principle: (1) Use an impact hammer to trigger the brake pad and measure the response using a microphone or accelerometer. Use an FFT analyzer to calculate the frequency response function (FRF) to obtain the resonant frequency and corresponding amplitude.

[0081] (2) Find the resonance peak on the FRF curve and record the resonance frequency (i.e. the frequency corresponding to the peak value of the resonance peak).

[0082] (3) On both sides of the resonance peak, find the frequency points where the amplitude drops by 3 dB. The frequency range between these two frequency points is called the half-power bandwidth, denoted by Δf.

[0083] (4) The damping rate η (i.e., DPR value) is calculated using the following formula: η = Δf / f.

[0084] (5) The above data can be read directly from the detector.

[0085] Where Δf is the half-power bandwidth (Hz) and f is the resonant frequency (Hz).

[0086] The test results are the average of four measurements, and the results are shown in Table 2.

[0087]

[0088]

Friction pair performance test

[0089]

[0090] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high damping base material, characterized in that: The preparation method comprises the following raw materials in parts by weight: 10 to 40 parts of nitrile rubber, 4 to 10 parts of phenolic resin powder, 30 to 50 parts of composite reinforcing fiber, 0.5 to 5 parts of zinc powder, 10 to 40 parts of filler, 0.6 to 2.3 parts of compatibilizer, and 0.2 to 4 parts of curing accelerator; The composite reinforcing fiber comprises para-aramid pulp, porous hydrated calcium silicate and metal fiber; wherein the mass ratio of the para-aramid pulp: the porous hydrated calcium silicate: the metal fiber is 1:2-7:3-10; The metal fiber is composed of 5-30% brass fiber, 3-20% aluminum fiber and the balance steel wool by mass fraction; The brass fiber and steel wool are soaked in a silane coupling agent and then dried, and then aluminum fiber is added and mixed to obtain metal fiber; The fiber length of the para-aramid pulp is 0.5-1.5 mm; The fiber specific area of ​​the para-aramid pulp is 5 to 13 m 2 / g; The chemical composition of the steel wool includes, by mass, C: 0.07-0.12%, Si≤0.07%, Mn: 0.8-1.25%, S≤0.03%, P≤0.03%; The brass fiber has a compacted volume of 0.5-0.8 mL / g; The outer diameter of the aluminum fiber is 8-30 μm; The elongation of the aluminum fiber is ≥2%.

2. The high damping base material according to claim 1, characterized in that: Meet at least one of the following conditions ①~④: ① The phenolic resin powder is thermosetting phenolic resin or modified phenolic resin powder; ② The particle size of the phenolic resin powder is ≤75 μm; ③ The filler is at least one of barium sulfate, calcium carbonate, mica powder and zinc oxide; ④ The particle size of the filler is ≤45μm.

3. The high damping base material according to claim 2, characterized in that: The modified phenolic resin powder is rubber modified phenolic resin powder, silicon modified phenolic resin powder or cashew nut shell oil modified phenolic resin powder.

4. The high damping base material according to claim 1, characterized in that: Meet at least one of the following conditions ①~③: ① The compatibilizer is a maleic anhydride grafted compatibilizer or a silane coupling agent; ② The curing accelerator is a urotropine curing agent; ③ The raw materials for preparing the high damping base material may further include an auxiliary agent, and the auxiliary agent is at least one of a colorant, a flame retardant and an antioxidant.

5. The method for preparing the high damping base material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Pre-treating brass fiber and steel wool, and then adding aluminum fiber to the mixture to obtain metal fiber: the pre-treatment is to soak the brass fiber and steel wool in a silane coupling agent with a mass fraction of 5-10% for 5-10 minutes and then dry the pre-treatment; S2. The nitrile rubber is plasticized, and then the other raw materials for preparing the high damping base material are subjected to low-temperature mixing, calendering and cooling to obtain a rubber block; S3. The rubber blocks are crushed and sieved to obtain high damping base material.

6. The method for preparing the high damping base material according to claim 5, characterized in that: Meet at least one of the following conditions ①~③: ① The low-temperature internal mixing and the plasticizing are both carried out in an internal mixer, and the temperature in the internal mixing chamber during the low-temperature internal mixing and plasticizing is ≤120°C; ② The plasticating time is 5 to 20 minutes; ③ The low-temperature mixing time is 5 to 30 minutes.

7. The method for preparing the high damping base material according to claim 6, characterized in that: The rotation speed of the internal mixer is 10-80 rpm, the compacting pressure of the internal mixer is 0.5-1.5 MPa, and the filling factor of the internal mixer is 0.8-2.5 times.

8. The method for preparing the high damping base material according to claim 5, characterized in that: Meet at least one of the following conditions ①~⑤: ① The roller speed of the calendering is 25~60rpm; ② The roller temperature of the calendering molding is 50~90℃; ③ The roller spacing of the calendering is 0.5~2mm; ④ The cooling water temperature used for cooling is 20~30℃; ⑤ The particle size of the screening is ≤3mm.

9. Use of the high damping base material according to any one of claims 1 to 4 or the high damping base material prepared by the preparation method according to any one of claims 5 to 8 in a friction plate, characterized in that: The friction plate includes a steel back, the high damping base material and a friction material surface from bottom to top; The thickness of the steel back is 4-6 mm; the thickness of the high damping base material is 2-2.5 mm; and the thickness of the friction material surface is 8-15 mm.

10. The use of the high damping base material in a friction plate as claimed in claim 9, characterized in that: The preparation of the friction plate comprises the following steps: spreading the high damping base material and the friction material surface material flat and covering them on the surface of the glue-coated steel back, and then performing hot pressing and curing to obtain the friction plate.

Citation Information

Patent Citations

  • Friction braking plate for pneumatic clutch and preparation method thereof

    CN101880435A

  • Composite fiber high-performance friction material and preparation method thereof

    CN111410936A

  • Environment-friendly friction material for electromagnetic brake and preparation method thereof

    CN117380953A

  • Brake friction material

    JP2008057693A

  • Friction material for brakes

    US20110297496A1